2009
DOI: 10.1016/j.jsv.2008.06.011
|View full text |Cite
|
Sign up to set email alerts
|

Energy harvesting from the nonlinear oscillations of magnetic levitation

Abstract: This paper investigates the design and analysis of a novel energy harvesting device that uses magnetic levitation to produce an oscillator with a tunable resonance. The governing equations for the mechanical and electrical domains are derived to show the designed system reduces to the form of a Duffing oscillator under both static and dynamic loads. Thus, nonlinear analyses are required to investigate the energy harvesting potential of this prototypical nonlinear system. Theoretical investigations are followed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
593
0
3

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 846 publications
(600 citation statements)
references
References 14 publications
4
593
0
3
Order By: Relevance
“…Alternatively, the intentional introduction of stiffness nonlinearity into the harvester design is a feasible way to offer broadband or multiple resonant responses, which can provide a wider application in different environments [6][7][8][9][10][11][12][13]. Usually Duffing-type harvesters under Gaussian white noise have been widely considered currently [2,14].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Alternatively, the intentional introduction of stiffness nonlinearity into the harvester design is a feasible way to offer broadband or multiple resonant responses, which can provide a wider application in different environments [6][7][8][9][10][11][12][13]. Usually Duffing-type harvesters under Gaussian white noise have been widely considered currently [2,14].…”
Section: Introductionmentioning
confidence: 99%
“…Usually Duffing-type harvesters under Gaussian white noise have been widely considered currently [2,14]. The Duffing-type harvesters can be adopted as either a mono-stable Duffing oscillator with a hardening/softening nonlinearity [6,9,15] or a bi-stable Duffing oscillator with a double-well potential energy function [7]. To model the nonlinear energy harvesting, a set of coupled equations between a randomly excited spring-mass-damper system and a capacitive energy harvesting circuit using a linear electromechanical coupling coefficient [1,2,16].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, most currently reported cantilevers operate at frequencies higher than 50 Hz (Marin, Bressers, and Priya 2011). Furthermore, cantilever-based devices are generally devoid of broadband behavior at their resonance frequencies, therefore limiting their capability outside the resonance region (Mann and Sims 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have identified broadband response and high power response from different forms of nonlinear magnet-based energy harvesters. A small subset of these studies (Dallago, Marchesi, and Venchi 2010;Mann and Sims 2009;Saha et al 2008) have reported a more direct method of harvesting energy by magnetic levitation of a magnet (or magnet composite) between two stationary magnets placed in a repelling direction to the magnet composite. Tornincasa et al (2012) analyzed this configuration for energy scavenging in automotive tires.…”
Section: Introductionmentioning
confidence: 99%
“…Variations around the Duffing oscillator provide several interesting possibilities. 7 Mann and Stanton et al 8,9 exploited hardening monostable oscillators to improve the effectiveness of energy harvesting devices under certain forms of periodic excitation. Moreover, the merits of harvesting energy from a periodic excitation source using a bistable nonlinear oscillator were also assessed.…”
Section: Introductionmentioning
confidence: 99%